Laminitis in dairy goats (Capra aegagrus hircus) on a low‐forage diet. Issue 4 (27th December 2018) - Groenevelt, Margit; Cahalan, Stephen D; Anzuino, Katharine; Hunt, Nicholas; Lee, Michael; Grogono‐Thomas, Rose
Abstract : Dairy goats on high‐concentrate diets attain high production levels, but at what cost? Here, ongoing lameness problems in a herd offered ad lib concentrates and roughages throughout their lifetime were investigated. Five severely affected, chronically lame animals were euthanased and examined postmortem. Foot pathology consisted of distortion of the claw shape and irregular fissures over the solar and bulbar horn with the distal phalanx rotated downwards on two claws. Rumen pH was measured between 5.26 and 5.46 with moderate rumen mucosa hyperkeratosis, and ulcerative, mild lymphocytic rumenitis. Feet showed irregular hyperplasia of the epidermal laminae with parakeratotic hyperkeratosis, especially in solar regions. Dense clusters of lymphocytes expanded the dermal laminae. Based on these findings, chronic laminitis was suspected. Ruminal hyperkeratosis was likely a result of prolonged periods of acidosis. The consequences of feeding a high‐concentrate ration throughout the life of dairy goats need more research.